-15n+17=-14n-2

Simple and best practice solution for -15n+17=-14n-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -15n+17=-14n-2 equation:


Simplifying
-15n + 17 = -14n + -2

Reorder the terms:
17 + -15n = -14n + -2

Reorder the terms:
17 + -15n = -2 + -14n

Solving
17 + -15n = -2 + -14n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '14n' to each side of the equation.
17 + -15n + 14n = -2 + -14n + 14n

Combine like terms: -15n + 14n = -1n
17 + -1n = -2 + -14n + 14n

Combine like terms: -14n + 14n = 0
17 + -1n = -2 + 0
17 + -1n = -2

Add '-17' to each side of the equation.
17 + -17 + -1n = -2 + -17

Combine like terms: 17 + -17 = 0
0 + -1n = -2 + -17
-1n = -2 + -17

Combine like terms: -2 + -17 = -19
-1n = -19

Divide each side by '-1'.
n = 19

Simplifying
n = 19

See similar equations:

| 7.8=23.4 | | 5(9.5-8h)=-20.5 | | 18-22=120 | | 4-11=120 | | 20a^2-15a= | | 3k+4+6k=-8+8k | | 3-8=35 | | m-4=22 | | 5+5+5=3x | | 17x-7+20x+15x+12x-17=360 | | 4ax-3b=b+20 | | -8d=80 | | 2-u=78 | | 7-9[7-(7y-4)]=0 | | x^4-2x^3+6x^2+8x-27=0 | | 11-18=63 | | -59+-2x=21-7x | | 4+3n=61 | | -[7z-(12z+4)]=4+(4z+1) | | (7p+2)3+8p= | | 8p^2+37p-15=0 | | 6+2=72 | | -10+5(c-3)=20 | | 2-(4x-7)=9-4x | | 3.5h+10=5.25h-10.25 | | 10x^2=2x+1 | | 9n^2-33n+28=0 | | -9(8+m)-13=-25 | | 9+8=15 | | 9-2=56 | | 7(x-4)+2=-19 | | -4.6+1.6=0.6 |

Equations solver categories